DESIGN,ANALYSIS AND SIMULATION OF A NOVEL QUASI-ZERO STIFFNESS VIBRATION ISOLATION SYSTEM - LAN Shuang; YANG XiaoXiang (Jixie qiangdu)
Combining a negative stiffness mechanism composed of tension spring with a linear positive stiffness spring in parallel,a novel quasi-zero stiffness vibration isolation systemwas designed which can be used to isolate low or ultra-low vibration. The static model of the system was established and the condition of quasi-zero stiffness characteristics was obtained.The fore-displacement curves of the tension-type isolator and a compression-type isolator were compared. The effect of adjustment of vertical spring in the system was analyzed. The dynamic equation was established when the system was excited by a harmonic amplitude on the displacement and the equation was solved by using Harmonic Balance method. The displacement transmissibility curves of the tension-type and the compression-type isolators were also compared. The effect of the main parameters on response of the system was explored. ADAMS model was established and the static model was proved to be correct. The vibration simulation results prove that the quasi-zero stiffness system has greater advantage than linear system in low or ultra-low vibration isolation.